Oxidative and antioxidative stress markers in dry eye disease: A systematic review and meta‐analysis. Issue 1 (2nd May 2021) - Navel, Valentin; Sapin, Vincent; Henrioux, Fanny; Blanchon, Loïc; Labbé, Antoine; Chiambaretta, Frédéric; Baudouin, Christophe; Dutheil, Frédéric
Abstract: Purpose: To conduct a systematic review and meta‐analysis on the levels of oxidative stress markers and antioxidants in dry eye disease (DED) compared with healthy subject. Method: The PubMed, Cochrane Library, Embase, Science Direct and Google Scholar databases were searched on 10 January 2021 for studies reporting oxidative and antioxidative stress markers in DED and healthy controls. Main meta‐analysis was stratified by type of biomarkers, type of samples (tears, conjunctival cells or biopsies), Sjögren's syndrome (SS) (patients with or without SS) and by geographical zones (Asia or Europe). Results: We included nine articles, for a total of 333 patients (628 eye samples) with DED and 165 healthy controls (451 eye samples). There is an overall increase in oxidative stress markers in DED compared with healthy controls (standard mean deviation = 2.39, 95% confidence interval 1.85–2.94), with a significant increase in lipid peroxide (1.90, 0.69–3.11), myeloperoxidase (2.17, 1.06–3.28), nitric oxide synthase 3 (2.52, 0.95–4.08), xanthine oxidase/oxidoreductase (2.41, 1.40–5.43), 4‐hydroxy‐2‐nonenal (4HNE) (4.75, 1.67–7.84), malondialdehyde (3.00, 2.55–3.45) and reactive oxygen species (1.31, 0.94–1.68). Oxidative stress markers were higher in tears, conjunctival cells and conjunctival biopsies of DED than controls. Even if small number of studies were included for antioxidants, catalase seemed to be decreased in DED compared with healthy controls (−2.17, −3.00 to −1.34), with an increase of antioxidants in tears of DED patients without SS (1.13, 0.76–1.49). Conclusion: Oxidative stress markers, and probably antioxidants, were dysregulated in DED, establishing a local oxidative environment in tears, conjunctival cells and tissues.